Evaluation of the intraventricular hemodynamics of patients with left ventricular dysfunction via vector flow mapping - Xu, Qun; Hao, Li; Yang, Guang; Zhang, Mei; Di, Mingxue (Frontiers in Cardiovascular Medicine, 2025)
BackgroundVorticity, measured via new vector flow mapping (VFM), a quantitative marker of vortex dynamics, can reflect hemodynamic changes more sensitively, potentially offering complementary information to conventional echocardiographic indices of cardiac function.AimsWe investigated left ventricular hemodynamics in both normal subjects and patients with left ventricular dysfunction to explore the probability of evaluating cardiac function with the assistant index, the highest vorticity value of a vortex (Vort-max).MethodsSixty subjects were divided into 3 groups, namely, the control group, Group I (HFpEF) and Group II (HFmrEF&HFrEF), and examined via conventional echocardiography. VFM was performed from the apical 5-chamber view to calculate the vorticity during diastole and systole in the left ventricle.ResultsHemodynamic changes were obvious during diastolic dysfunction. The Vort-max-base values of early and late diastole in Group I were greater than those in the control groups (P < 0.001). The Vort-max-apex of mid-systole in Group I was greater than that in the control group (P = 0.044). Vort-max-base in early diastole, Vort-max in all three segments in mid-diastole, Vort-max-apex and Vort-max-middle in late diastole, were associated with E/e′ and E (P < 0.05). Vort-max-middle and Vort-max-base in all three segments in late diastole was associated with A (P < 0.05).ConclusionsBlood flow energy was detected in patients with diastolic and systolic dysfunction by using Vort-max derived from vector flow mapping. The vorticity value could be a novel parameter for evaluating the hemodynamic changes in the left ventricular cavity and cardiac diastolic function.